2023
DOI: 10.55188/ijif.v15i2.540
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z’s Financial Behaviour: The Role of Islamic Financial Literacy

Abstract: Purpose — This research aims to examine the effect of family communication patterns on Islamic financial literacy (IFL) and risk tolerance of Generation Z (Gen Z) in Indonesia. It also examines the link between IFL, risk tolerance and financial behaviour. Finally, it highlights the moderating impact of IFL on the link between risk tolerance and financial behaviour. Design/Methodology/Approach — This study used Muslim members of Gen Z in West Sumatra Indonesia who were born between 1995 and 2001 as the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The findings showed that differences in financial literacy among the generations have a significant impact on their investment decisions. It was concluded that financial literacy and investment experience are vital for successful capital market investments and in line with previous studies results (see for example: Patrisia et al, 2023;Sherwood, 2020). Fungáčová et al (2020) have studied Does the type of debt matter?…”
Section: Review Of Literaturesupporting
confidence: 88%
“…The findings showed that differences in financial literacy among the generations have a significant impact on their investment decisions. It was concluded that financial literacy and investment experience are vital for successful capital market investments and in line with previous studies results (see for example: Patrisia et al, 2023;Sherwood, 2020). Fungáčová et al (2020) have studied Does the type of debt matter?…”
Section: Review Of Literaturesupporting
confidence: 88%
“…The varying levels of investor comprehension and capabilities in the Islamic capital market result in differing levels of risk perception among investors in this sector. This is confirmed in the studies of Aren and Hamamci (2022), Suherman et al (2023), and Patrisia et al (2023), which have proven that the increase in risk perception is influenced by Islamic capital market literacy.…”
Section: Risk Perceptionsupporting
confidence: 64%
“…As such, Generation Z will feel more confident in their ability to plan and mitigate investment risks. This is verified in the research of Aren and Hamamci (2022), Suherman et al (2023), andPatrisia et al (2023), proving that the increase in risk perception is influenced by Islamic capital market literacy.…”
Section: The Effect Of Islamic Capital Market Literacy On Risk Percep...mentioning
confidence: 55%
“…The research [10] which explores the level of Islamic financial literacy among women in Indonesia and Malaysia, [11] about the Islamic financial literacy index among students. Besides that, the research [12] explains the level of Islamic financial literacy of generation Z in West Sumatra which is significantly influenced by communication patterns within the family. And the research [13] which uses Muslim millennials as research objects on the level of Islamic financial literacy using the RASCH analysis method.…”
Section: Figure 1 Level Of Transactions Using Digital Wallets or E-wa...mentioning
confidence: 99%
“…This is the indicator of Islamic financial literacy that people, especially Muslims, should pay attention to. Islamic financial literacy, in summary, can be measured from 4 (four) dimensions, namely the ability to manage finances (money basics), use of sharia banking, Islamic investment behavior, and takaful [12], or protection of assets [25].…”
Section: O You Who Believe Do Not Devour Each Other's Wealth In a Fal...mentioning
confidence: 99%